A implementação do REUNI no Centro de Ciências Agrárias da UFES : trabalho, gestão e ideologia vistos pelos professores - Martins, Raisa Maria de Arruda (2017)
This paper refers to a case study whose main objective is to be acquainted with the beliefs of professors in the Agricultural Science Center (CCA) in the Federal University of Espírito santo (UFES) towards their working conditions concerning the implementation of the Program to Support Restructuring and Expansion Plans of Federal Universities (REUNI). In this perspective, the working conditions described by the professors are considered mediations which have made possible to know how faculty understands the university from the expansion process, its role, and teaching staff themselves. First, the study characterizes REUNI, pointing out the program in the extent of the previous regulation marks, such as in the legislation approved after its validity was over, indicating, therefore, the prolongation of its goals through the next years. The contradictions of the program and its critics presented in the related literature were established. The result of REUNI’s expansion in Brazil, in UFES and particularly in CCA are as well presented. This stage has been constituted from the analysis of documents officially produced (by Government) and of those elaborated by UFES concerning REUNI, such as the institution’s expansion plan, the CCA’s council’s meetings’ records, and the indices of the courses’ performances in this Center while REUNI was in force. Second, the speeches of the professors of the same Center were resorted to, in order to see the light of the repercussion concerning the University’s expansion in its everyday work. Therefore, interviews were developed with 12 professors, 5 of which were hired before the expansion. As empiric data is analyzed, as well as considering the reporting of the working conditions exposed by the teaching staff, it is possible to observe that indeed the expansion induced by REUNI has promoted meaningful changes in CCA, which for many years had only had one undergraduation course, but had its offer enlarged to seventeen courses in seven years (from 2006 to 2012, through the plans Expansion Phase 1 and REUNI). Such changes included both administrative and academic dimensions (increase of vacancy offers, new courses, hiring professors, buildings’ and laboratories’ construction etc.). Amongst other matters, it is possible to verify that the group of professors recruited between 2006 and 2012 were the most affected by the changes provoked by the expansion, so that it is possible to consider that these professionals work under precarious conditions and even intensified work conditions. However, it is impossible to affirm the same about the working conditions of those who already were part of the faculty before the expansion process. Amongst the likely findings, it is verified that the shape assumed by REUNI in CCA is a result of the policy formulated concatenated to the aspects that confer specificity to the institution. Finally, it is also possible to verify that the meaning attributed to the expansion reflects how contradictory REUNI is, and may, as in CCA case, assume different significance for the professors, as the teaching staff is heterogeneous and, therefore, constituted by groups with distinguished characteristics.